ANALISIS WEBSITE E-GOVERNMENT PROVINSI BENGKULU MENGGUNAKAN WEBQUAL 4.0 - -, Diana (Jurnal Informatika, 2014)
Analysis of the quality of the e-government website is very important to be studied. WebQual 4.0 is a method used to measure the quality of a website based on user perception. Parameter WebQual 4.0 consists of usability, quality of information, and service interactions. The data collection is done by distributing questionnaires to 30 students in the province of Bengkulu. Website sampled is website Bengkulu province. The study of Bengkulu province website indicates that the respondents agree with the usability of the website, of sufficient quality and do not agree to the service interaction. Assessment of the overall Bengkulu website is of sufficient quality. Based on the results of questionnaires usability gained 3.92 score, the quality of information obtained score 3:00, 2:47 score obtaining service interaction, and the overall gain score 3:13.Keywords: websites, e-government, WebQual 4.0, usability, quality of information, interaction services